(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Biochemical changes along with microbial contamination may shorten the shelf life of post harvested fruits and vegetables. Generally, various physical and chemical treatments are being used to preserve the post harvested fruits. However, those treatments are hardly good for human health as well as the environment. Interestingly, lactic acid bacteria (LAB) produce antimicrobial peptides that are harmful to food spoilage bacteria and extend shelf life by killing them. Therefore, the present study is designed to investigate spontaneous fermentation by the autochthonous LAB in the cabbage leaves and the application of fermented cabbage extract to enhance the shelf-life of banana fruits. The result showed that the fermented cabbage extract was acidic (pH = 3.6 after 40 hours) in nature and increased its acidity over time. In 24 hours, 1 mgL-1 lactic acid was produced by LAB in cabbage leaves. In fermented cabbage extract, 3.85 mg per 100g vitamin-C was measured, antioxidant properties expressed by the DPPH and it was 3.02 mgml-1. Anthocyanin and flavonoids were present in cabbage extract but no tannin was observed. After 48h fermentation, the fermented cabbage extract was applied immediately to the harvested mature banana fruits. The brown surface of the banana was considered as an indicator before rotting. The brown surface in the control banana appeared on Day 7 after exposing to cabbage extract. On the other hand, such surface appeared on treated banana on Day 11. By Day 11, control banana group had already succumbed to rot. This result indicates that the treated banana took an additional 4 days to reach the state. Taken all together, it may be concluded that fermented cabbage extract possesses a promising role to extend the shelf life of banana fruits and to reduce the postharvest loss through eco-friendly natural approach without compromising quality and safety. J Bangladesh Agril Univ 22(2):241-248, 2024